2022
DOI: 10.1038/s41467-022-29813-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity in ramp-compressed sodium to 480 GPa

Abstract: The properties of all materials at one atmosphere of pressure are controlled by the configurations of their valence electrons. At extreme pressures, neighboring atoms approach so close that core-electron orbitals overlap, and theory predicts the emergence of unusual quantum behavior. We ramp-compress monovalent elemental sodium, a prototypical metal at ambient conditions, to nearly 500 GPa (5 million atmospheres). The 7-fold increase of density brings the interatomic distance to 1.74 Å well within the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In addition, first principles molecular dynamics simulations at temperatures typical of those accessed using ramp-compression experiments (1500 K at 260 GPa, and 2000 K at 315 GPa, see Section S7), revealed that the (refined) atomic configurations in P 6 3 /m Na, including the soon-tobe-discussed honeycomb channels, are thermally stable. At 400 GPa Na hP 4 possessed the lowest Gibbs free energy to at least 3500 K (Figure S7), in agreement with experimental diffraction data that could be attributed to this phase at 409 ± 15 GPa [7].…”
supporting
confidence: 87%
See 4 more Smart Citations
“…In addition, first principles molecular dynamics simulations at temperatures typical of those accessed using ramp-compression experiments (1500 K at 260 GPa, and 2000 K at 315 GPa, see Section S7), revealed that the (refined) atomic configurations in P 6 3 /m Na, including the soon-tobe-discussed honeycomb channels, are thermally stable. At 400 GPa Na hP 4 possessed the lowest Gibbs free energy to at least 3500 K (Figure S7), in agreement with experimental diffraction data that could be attributed to this phase at 409 ± 15 GPa [7].…”
supporting
confidence: 87%
“…However, at the high temperatures consistent with those attained in rampcompression experiments, the P 6 3 /m phase was computed to possess the lowest Gibbs free energy between 250 GPa (above 710 K) and 350 GPa (above 1900 K). Above 400 GPa, Na hP 4 again became preferred, in agreement with experimental observations [7]. At 200 GPa (350 GPa) the newly discovered P 6 3 /m structure was computed to be more stable than Na hP 4 above 150 K (1900 K) (Figure 1(b)).…”
supporting
confidence: 86%
See 3 more Smart Citations